2019
DOI: 10.2139/ssrn.3435106
|View full text |Cite
|
Sign up to set email alerts
|

Urban Agglomerations and Firm Access to Credit

Abstract: The paper investigates whether firms have better access to bank credit in areas with a larger degree of urbanization. It uses bank-firm data drawn from the Credit Register maintained at the Bank of Italy to devise an indicator of ease of access to credit. The paper proposes an instrumental variable strategy that uses as instruments past population density and urbanization driven by considerations of political economy. The results show that urbanization affects access to credit positively for construction firms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This is a well-known phenomenon even for access to banking. Several contributions show that firms in areas with higher agglomeration have better access to bank credit (Carmignani et al, 2019;Ganau, 2016;Lee and Brown, 2017;Mayer et al, 2021;Lee and Luca, 2019). Nonetheless, this geographical issue is certainly tighter for nonbank financing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a well-known phenomenon even for access to banking. Several contributions show that firms in areas with higher agglomeration have better access to bank credit (Carmignani et al, 2019;Ganau, 2016;Lee and Brown, 2017;Mayer et al, 2021;Lee and Luca, 2019). Nonetheless, this geographical issue is certainly tighter for nonbank financing.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, local financial markets are especially important, given the high levels of geographic segmentation of these markets and the provincial concentration of high-performing firms. Although even this paper looks at the characteristics of the local banking sector, it examines how firm location is instrumental to the access of capital markets, while most contributions focus strictly on bank credit access (Moretti, 2014;Ganau, 2016;Carmignani et al, 2019). Distance is measured considering access to transportation networks, as recent literature has shown that it can have a direct effect on the quality of management (Baltrunaite and Karmaziene, 2021) where decisions to access capital markets are taken.…”
Section: Introductionmentioning
confidence: 99%
“…This is a well-known phenomenon even for access to banking. Several contributions show that firms in areas with higher agglomeration have better access to bank credit (Carmignani et al, 2019;Ganau, 2016; 1 See also https://www.brookings.edu/blog/up-front/2022/01/20/gone-digital-technology-diffusion-in-the-digital-era/ 2…”
Section: Introductionmentioning
confidence: 99%
“…This is a well‐known phenomenon even for access to banking. Several contributions show that firms in areas with higher agglomeration have better access to bank credit (Carmignani et al, 2019; Ganau, 2016; Lee & Brown, 2017; Lee & Luca, 2019; Mayer et al, 2021). Nonetheless, this geographical issue is certainly tighter for nonbank financing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation